Development of a Strategic Decision-Making Framework for Transitioning to a Circular Economy in Mining: A Hybrid SWOT–Fuzzy VIKOR Approach - Bardideh, Amirreza; Naseri, Aynur; Poormirzaee, Rashed; Taghizadeh, Rahim (Management Strategies and Engineering Sciences, 2026)
The transition to a circular economy (CE) in the mining industry constitutes a complex decision-making challenge that confronts managers with conflicting objectives (economic, environmental, and social) and data uncertainty. This study aims to bridge the gap between theory and practice by proposing an innovative hybrid framework (SWOT–Fuzzy VIKOR) for prioritizing CE strategies. The proposed framework integrates qualitative expert analysis through SWOT analysis and the formulation of TOWS strategies with the quantitative evaluation of a fuzzy multi-criteria decision-making model (Fuzzy VIKOR). The research was conducted as a case study in a copper mining complex located in the northwest of the country. The results indicate that strategies based on human capital development (M1), with a score of Q = 0.00, and stakeholder management (M2), with a score of Q = 0.49, are identified as the primary priorities. These findings suggest that, prior to making large-scale technical investments, managers should focus on strengthening human and social infrastructures as essential prerequisites for a successful transition toward sustainability. This framework provides a practical and robust tool for strategic decision-making in heavy industries.